A PRACTICAL method to detect a transverse cracked rotor using transient response - Wang, Xiaofeng (Strojniški vestnik, 2017)
To detect a transverse crack caused by fatigue or creep, most of the research has thus far paid attention only to resonances of steady-state oscillations created by the crack and proposed diagnosis systems utilizing these vibration phenomena. However, from a practical view point, these diagnosis systems have the following flaws: (1) the probability that a resonance occurs due to a crack in the rated rotational speed range is a lower position; (2) It is very dangerous to observe vibration characteristics in resonance ranges. In order to solve these problems, this paper uses a practical detection method utilizing the characteristic changes in a transient oscillation during the start-up, the shutdown, or the variable running speeds of rotating machinery. This method has great advantages, because it can check the occurrence signals of a crack in a wide speed range using a single sweep and avoid the operation in dangerous resonance ranges. Non-stationary characteristics during passages through the main resonance and various kinds of resonances are studied numerically and experimentally.
Keywords: diagnostična metoda; eksperimenti; motor z razpoko; nelinearno; prehodni odgovor; vibracijske lastnosti